Synergy between microalgae and microbiome in polluted waters. Issue 1 (January 2023) - Ashraf, Noreen; Ahmad, Fiaz; Lu, Yandu
Abstract : Microalga–microbiome interactions are central to both health and disease of aquatic environments. Despite impressive advances in deciphering how microorganisms participate in and impact aquatic ecosystems, the evolution and ecological involvement of microalgae and the microbiome in polluted waters are typically studied independently. Here, the phycosphere (i.e., the consortia of microalgae and the related microbiome) is regarded as an independent and integrated life form, and we summarize the survival strategies exhibited by this symbiont when exposed to anthropogenic pollution. We highlight the cellular strategies and discuss the modulation at the transcriptional and population levels, which reciprocally alters community structure or genome composition for medium-term acclimation or long-term adaptation. We propose a 'PollutantBiome' concept to help the understanding of microalga–microbiome interactions and development of beneficial microbial synthetic communities for pollutant remediation. Highlights: Microalga–microbiome interactions are central to aquatic environments. The phycosphere is the consortia of microalgae and the related microbiome. Molecular signals connect microalgae and their microbiome as a whole. Dynamics of community structure and horizontal gene transfer in the phycosphere facilitate midterm acclimation and long-term adaptation to pollutants. Well-designed microalga–microbiome cocktails help pollutant remediation.